THE INFLUENCE OF DIGITAL MEDIA ON STUDENT MOTIVATION IN THE CLASSROOM - Qosimova Mavluda Navruzovna (Modern American Journals, 2025)
Continuous digitization is profoundly transforming the education system and at the same time opening up new didactic scope for design. The aim of this article is to analyse the influence of digital media on the learning motivation of pupils in the school context in a differentiated way. The analysis is based on a methodologically sound mixed-methods approach that integrates both qualitative and quantitative research elements. Particular attention is paid to the pedagogical framework conditions under which digital media can unfold their motivating effect. The findings of the study show that digital technologies – depending on their didactic integration and functional objectives – can have both beneficial and inhibiting effects on the motivation of learners.